Exploring internal challenges and coping strategies in online English learning via Google Meet: A study of 7th grade students in Yogyakarta - Pratolo, Bambang Widi; Beliarita, Liza; Alsulami, Naif Daifullah (BAHASTRA, 2024)
Google Meet is widely used application for distance learning, but its use presents both external and internal challenges for students. This study focuses solely on the internal challenges faced by students. The aim of this research is to identify the problems encountered in using Google Meet for online English learning and to explore the strategies students employ to overcome these issues. The study was conducted with seventh-grade students from a private junior high school in Yogyakarta. A descriptive qualitative method was used, with eight seventh-grade students participating as research subjects. Data were collected through interviews and documentation, with pseudonyms used to protect students' privacy. The research identified several key internal challenges, including a lack of motivation, difficulties interacting with teachers and peers, challenges in maintaining focus, reduced confidence in using Google Meet, and difficulties with group assignments. In response to these challenges, students implemented various strategies, such as taking notes on material presented by the teacher, seeking further clarification from teachers or classmates, completing assignments on time, being more active and communicative during lessons, and strengthening their focus and attention. The findings of this study suggest that educators need to be aware of the internal challenges students face when using digital tools like Google Meet for online learning. Schools and teachers may need to provide more guidance and support to help students stay motivated and engaged in virtual classrooms. Additionally, developing student-centered strategies to enhance interaction and improve focus during online sessions is essential for ensuring effective learning outcomes.